Pengaruh Teknik Pembersihan Dan Wadah Penyimpanan Terhadap Preferensi Serangga Hama Lanas (Cylas formicarius Fabricius) Dan Kualitas Ubi Jalar (Ipomoea batatas (L). Lam) CV. Cilembu - Herawati, Lia; Roosma Ria , Elly; Amalia, Lia (OrchidAgro, 2024)
Farmers who have been cultivating sweet potatoes have complained about the large number of pest attacks which can cause a decrease in the quality of their harvest. The storage of Cilembu sweet potatoes currently carried out by farmers is still traditional. The aim of this research was to study the interaction between cleaning techniques and storage containers on the preferences of lanas insect pests and the quality of Cilembu sweet potatoes. The research was a factorial experiment with two factors and three replications using the Completely Randomized Design (CRD) method. The first factor is the technique of cleaning sweet potatoes using conventional water spraying (c1), brushing sweet potatoes using a coconut fiber brush (c2), soaking using foodgrade liquid soap (c3) and quick dipping in 10 mL-1 neem solution (c4). The second factor, storage in a container with a gauze lid to provide air circulation (s1) and a container with a tight lid (s2). Data were analyzed using analysis of variance analysis of variance (ANOVA) with a level of 5%. The experimental results showed that there was an interaction on the preference level parameters of the lanas insect pest. The cleaning technique using quick dipping of sweet potatoes that have been washed and stored in a gauze container can reduce the preference of lanas insects to eat and lay eggs. By lowering the level of pest attacks, the quality of sweet potatoes will be better maintained. Keywords: Sweet Potatoes, Cleaning Techniques, Storage Containers, Azadirachta indica